APOL1 genotypes: Do they contribute to ethnicity-associated biological health inequalities in pregnancy?. (December 2022) - Smith, Priscilla; Bramham, Kate
Inferior health outcomes for people of African and Afro-Caribbean ancestry compared to those of European ancestry are well recognised. There is a disproportionate impact within these communities compared to other ethnic groups including pregnancy outcomes, hypertension, kidney disease and diabetes. The 'Black Lives Matter' movement has highlighted that it is imperative to examine all factors contributing to this inequity and to strive to explore multifaceted ways, including social, economic, psychological and biological to improve overall health equity. It is within this context that we discuss the novel finding of Apolipoprotein 1 genetic polymorphisms which have been identified in some populations of African ancestry. We will explore the history and evolutionary advantages of Apolipoprotein 1 polymorphisms and the pathophysiology resulting from these adaptations and examine the impact of Apolipoprotein 1 on pregnancy outcomes, the risks and benefits of screening for high-risk Apolipoprotein 1 alleles in black communities and potential treatments currently being investigated.